Imaging of Dopamine in PD and Implications for Motor and Neuropsychiatric Manifestations of PD - de la Fuente-Fernandez, Raul (Frontiers in Neurology, 2013)
Parkinson’s disease (PD) is characterized by dopamine depletion in the putamen, which leads to motor dysfunction. As the disease progresses, a substantial degree of dopamine depletion also occurs in caudate and nucleus accumbens. This may explain a number of neuropsychiatric manifestations, including depression, apathy, and cognitive decline. Dopamine replacement therapy partially restores motor function but long-term treatment is often associated with motor complications (motor fluctuations and dyskinesias). Positron emission tomography (PET) studies suggest that the dopamine release rate is substantially higher in PD subjects with motor complications compared to stable responders. Notably, this differential pattern of dopamine release is already present in the early stages of the disease, before motor complications become clinically apparent. Converging evidence suggests that striatal dopamine depletion in PD leads to reduced plasticity in the primary motor cortex and, presumably, in non-motor cortical areas as well. Although dopamine replacement therapy tends to restore physiological plasticity, treatment-induced motor, and neuropsychiatric complications could be related to abnormalities in corticostriatal synaptic plasticity.